2011
DOI: 10.1093/jjco/hyr046
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Operative Mortality and Post-operative Lethal Complications after Head and Neck Reconstruction with Free Tissue Transfer

Abstract: These results indicate that head and neck reconstruction with free flaps is reliable. However, the high 30-day post-operative mortality rate among patients 80 years or older should be considered when deciding whether to operate. To decrease the operative mortality rate, careful perioperative management is needed to prevent complications and shorten the hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…The 30-day mortality rates in our study were higher than those reported in the developed countries. Tanaka et al 8 reported mortality rates of 0.88 per 100 surgeries in Japan, and Pohlenz et al 9 reported intrahospital mortality of 1.0 per 100 surgeries in Germany. Our study found the 30-day mortality rate to range from 3.14 in Bogota to 4.29 in the Pacific region, per 100 surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…The 30-day mortality rates in our study were higher than those reported in the developed countries. Tanaka et al 8 reported mortality rates of 0.88 per 100 surgeries in Japan, and Pohlenz et al 9 reported intrahospital mortality of 1.0 per 100 surgeries in Germany. Our study found the 30-day mortality rate to range from 3.14 in Bogota to 4.29 in the Pacific region, per 100 surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…11,19 Knowledge of the cause of death after microvascular reconstruction in patients with HNC has been limited. Tanaka et al 26 analyzed the data from patients with HNC who had been treated with free flaps. They found a short-term (30-day) mortality of 0.88%; however, the long-term survival was not analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…They found a short-term (30-day) mortality of 0.88%; however, the long-term survival was not analyzed. 26 Lahtinen et al 27 retrospectively analyzed the survival and cause of death in 146 patients with head and neck free flap reconstruction at a median follow-up of 3 years. HNC was the primary cause of death in most (73%) patients, 27 in line with the results from the present study (79%).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the operative duration in the VBG group was significantly longer than those of the other two groups, and the volume of intraoperative blood loss tended to be greater than that of the MRP group. These differences may have little impact on young, healthy patients but can be critical in elderly patients and increase the risk of operative mortality . The indication of VBG for elderly patients should therefore be carefully evaluated by weighing its merits against various factors such as age, comorbidities, tumor status, and availability of donor sites.…”
Section: Discussionmentioning
confidence: 99%